Selling spectrum in the presence of shared networks: The case of the Israeli 5G auction. (March 2023) - Blumrosen, Liad; Solan, Eilon
Abstract: The Israeli 5G auction that took place in August 2020 used the Combinatorial Clock Auction mechanism adapted to the Israeli market. We review the challenges that the Israeli Ministry of Communication faced while designing the auction and discuss the strategic consequences of the design. We highlight the special characteristics of the Israeli telecommunication market and, in particular, the fact that most operators share their antenna networks and their spectrum assets with other auction participants, but spectrum licenses need to be purchased by each operator individually. The Israeli Ministry of Communication required operators sharing the same networks to submit joint bids in the auction. We discuss the implications of this decision on the efficiency of the auction, and the difficulties it caused the bidders. We discuss the effect of further incentive schemes that accompanied the auction, and we also describe some signaling opportunities that emerged during the auction process. Graphical abstract: Highlights: We review challenges faced by the Israeli MoC while designing the 2020 5G auction. We discuss strategic consequences of the auction design and the market structure. Some operators participate in the auction while sharing their spectrum assets. We study the implications of requiring participants to form joint-bid agreements. We discuss further incentive schemes and signaling opportunities in this auction.